APPLICATION OF THE TEAMS GAMES TOURNAMENT (TGT) MODEL IN GRADE V MATHEMATIC LEARNING - Utami, Alul Sri; Rarasati, Ida Putri; Putriani, Ida (Transpublika Publisher, 2022)
Mathematics is often perceived by students as a challenging subject due to its complicated calculations, resulting in a lack of interest. Despite the expectation that teachers should implement active learning methods, many still rely on traditional lecturing methods, leading to passivity in students. An analysis by the teacher showed that only 45% of students had completed their studies. To address this, a diverse learning approach is required, such as the Teams Games Tournament (TGT) learning model. The study aims to evaluate how the TGT learning model can improve grade V students' learning outcomes and attitudes towards mathematics. This study used qualitative and quantitative research techniques to measure student attitudes and learning outcomes, respectively. Classroom Action Research (CAR) techniques were employed by implementing two cycles with pre-tests and post-tests. In the first cycle, student completeness was 33% in the pre-test, while in the post-test, it increased to 73%. In the second cycle, the pre-test recorded 79% completeness, which increased to 85% in the post-test. The application of the TGT cooperative learning model improved student learning outcomes in each cycle, as evidenced by the increase in student completeness. These results support the effectiveness of the TGT model in improving student learning outcomes.